Impact of Macroeconomic Factors on Foreign Direct Investment (FDI): Evidence from ASEAN Countries - Rengasamy, Dhanuskodi (2015)
The main objective of this research is to examine the impact of various macroeconomic factors on foreign direct investment (FDI) inflow of the Association of Southeast Asian Nations (ASEAN) member countries. The selected macro-economic factors are gross domestic product (GDP), foreign exchange rate and inflation rate and these are independent variables of the study. FDI is determining through the amount of inflow during the study period and it is treated as a dependent variable. For the analysis the study undertakes the trend & growth analysis and applied Panel data analysis for 10 ASEAN countries over the period of five years from 2009 to 2013.The study conducted Pooled OLS model and random effect model. To identify the individual specific effect correlated with independent variable of the study applied fixed effect model. Finally the study applied Hausman test to find out the suitable model among the random effect and time effect. The result of the study stated that the trend and growth of FDI inflow is positive and progressive. The macro economic factors of GDP and inflation are significant and impact on FDI inflow, foreign exchange rate is not significant and there is no impact on FDI inflow. Keywords: Foreign Direct Investment, macroeconomic factors, ASEAN countries, Gross domestic product (GDP), foreign exchange rate and inflation rate